Originally Posted by

**mathmathmathmathmathmathm** (t - 1) ^-2/3 = 2

the answer is {4 - sqrt of 2 / 4}, {4 + sqrt of 2 / 4}

my steps:

1. raise each side a neg 3 to eliminate neg 2

2. the 2 becomes 1/8

3. apply even root property

t-1 = + or - 1 / (2 times sq rt of 2) and from there i know i screwed up. Any tips would be great.

The method in your Original Post looks fine as far as you went, with the addition of the above parentheses.

$\displaystyle t-1=\pm\frac{1}{2\sqrt{2}}$$\displaystyle =\pm\frac{\sqrt{2}}{4}$

Therefore, $\displaystyle t=1\pm\frac{\sqrt{2}}{4}\,.$

Added in **Edit**:

Looks like **mrmohamed** beat me to it.